2017
DOI: 10.2174/1573403x12666161222155230
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Bioabsorbable Polymer-Coated Drug-Eluting Stents

Abstract: Drug-eluting stents (DES) have been shown to significantly reduce clinical and angiograph-ic restenosis compared to bare metal stents (BMS). The polymer coatings on DES elute antiproliferative drugs to inhibit intimal proliferation and prevent restenosis after stent implantation. Permanent poly-mers which do not degrade in vivo may increase the likelihood of stent-related delayed arterial healing or polymer hypersensitivity. In turn, these limitations may contribute to an increased risk of late clinical events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 108 publications
0
10
0
Order By: Relevance
“…However, others have suggested that the improvements have not reduced the overall risk of late in-stent thrombosis, indicating that a different approach to stent design is needed ( Tada et al, 2013 ). Second generation drug-eluting stents are reviewed in detail in Ho et al (2016) and Akinapelli et al (2017) .…”
Section: Localized Drug Delivery From Vascular Stentsmentioning
confidence: 99%
“…However, others have suggested that the improvements have not reduced the overall risk of late in-stent thrombosis, indicating that a different approach to stent design is needed ( Tada et al, 2013 ). Second generation drug-eluting stents are reviewed in detail in Ho et al (2016) and Akinapelli et al (2017) .…”
Section: Localized Drug Delivery From Vascular Stentsmentioning
confidence: 99%
“…Despite the optimistic results of second-generation DESs, the evident improvements did not reduce the risk of delayed in-stent thrombosis [ 12 ], indicating that a different approach to the stent was needed in its design. Furthermore, the role of the second-generation drugs used in bioabsorbable polymer-coated DESs should be clarified [ 53 ]. Notably, with the exception of the PROTECT study, which compared the long-term outcomes of SES and PC-ZES usage [ 54 , 55 ], concerns related to the long-term safety and efficacy of second-generation DESs persist as they have not been evaluated or investigated by adequately powered studies.…”
Section: From Bare-metal Stents To Absorbable Stents: the Evolutiomentioning
confidence: 99%
“…PLGA degree of crystallinity and amorphousness depends on the type and ratio of the PLA and PGA monomers [160] Example: Synergy™ , MiStent SES® [27,160] Biodegradable Crystallinity and amorphousness can be adjusted based on the monomer ratio; e.g. higher content of PGA leads to faster degradation rates with an exception of 50:50 ratio of PLA/PGA (amorphous), which exhibits the fastest degradation; higher PGA/PLA ratio leads to increased degradation interval below 50% Increasing the lactic acid content yields a more crystalline polymer [161][162][163] Drug release rate is higher in polyesters with a low degree of crystallinity because of higher macromolecular chain mobility [164,165] However, PLGA degrades by bulk erosion associated with burst release [127,[166][167][168] Polymer degradation yields acidic products that can alter the pH and cause unfavorable inflammatory responses [34,35] PDLLA PLA has D-or L-stereochemical centers (or R or S, respectively), giving rise to two enantiomeric forms of PDLA or PLLA; PDLLA is completely amorphous [135] Biodegradable; however, PDLLA degrades by bulk erosion associated with burst release [127] PLLA PLA has D-or L-stereochemical centers (or R or S, respectively), giving rise to two enantiomeric forms of PDLA or PLLA; PLLA is highly crystalline [135] Example: Orsiro ® (PLLA bioabsorption takes 15 months, while drug is eluted in 3 months [169] Biodegradable; high MW PLLA undergoes slow degradation and erosion due to its high MW and chemical composition [127] PEVA: poly (ethylene-co-vinyl acetate); PBMA: poly(n-butylmethacrylate); PCh: phosphorylchlorine polymer; SIBBS Poly (styrene-bisobutylene-b-styrene); PVDF-HFP:poly(vinylidene-co-hexaflouropropylene); PLGA:Polylactic co-glycolic acid; PLLA: Poly L lactic acid Biodegradable polymers like PLA, PGA and PLGA, degrade by bulk erosion associated with burst release and subsequent inhibition of reendothelization associated with stent thrombosis [127,[166][167][168]. Synthetic PLA, although biocompatible, can take more than a year to degrade and therefore carries a risk of late and very late stent thrombosis [128,191].…”
Section: Plgamentioning
confidence: 99%
“…Synthetic PLA, although biocompatible, can take more than a year to degrade and therefore carries a risk of late and very late stent thrombosis [128,191]. In case of Orsiro (biodegradable DES system), it takes up to 15 months to degrade and is, therefore, present long after the drug has been eluted in the first three months [169]. Additional problems may arise from poor mechanical performance and generation of acidic products from polymer degradation, which may lead to inflammatory responses and induce neointimal hyperplasia and subsequent restenosis, as well as thrombosis at a lower pH [34,35].…”
Section: Plgamentioning
confidence: 99%